Phylogenomic analysis of Bupleurum in Western Sichuan, China, including an overlooked new species - Chao, Zhi; Hong, Xiaoxi; Xie, Xuena; Huang, Rong; Tian, Enwei (Frontiers in Plant Science, 2023)
A comparative analysis of chloroplast (cp) genomes and 45s nuclear ribosomal DNA (nrDNA), and a phylogenomic study of six closely related species (including an overlooked new species) of genus Bupleurum from the western part of Sichuan Province in southwestern China were performed. The six species are similar morphologically and it is difficult to identify them; moreover, their genetic relationships remain unclear. It was found that the cp genomes of the six Bupleurum species were extremely similar, and they were highly homogeneous in terms of cp genome structure, genes and its arrangement. Intergenic spacer rpl32-trnL, petA-psbJ, trnK-rps16, and the coding gene ycf1 were considered highly variable. In phylogenetic trees constructed based on the complete cp genome, protein-coding sequences, nrDNA and ITS sequences, Chinese Bupleurum species all formed two major clades; among these trees, nrDNA tree had the best species resolution; the highly variable regions showed no advantage over other molecular markers. Among the six Bupleurum species, B. malconense, B. sichuanense were close relatives to B. chinense and B. yinchowense, B. chaishoui may also be a consanguinity, while B. microcephalum, B. wenchuanense, and the new species B. pseudochaishoui were closely related. At the end, the new species B. pseudochaishoui Z. Chao sp. nov. was described and illustrated, and a key to the six species was tabulated.